Suplementação em atletas adolescentes. O que se sabe sobre a sua segurança e eficácia. Uma revisão da literatura - Gonçalo Miguel Leite Nogueira (2021)
Introduction: The pressure to which elite young athletes are subjected to leads to the search for alternative ways to achieve competitive advantage, being nutritional supplements and ergogenic substances an alternative that is often considered. Methods: Search in Web Of Science for articles from the last 20 years using the query: ((sport OR exercise) AND supplement AND teenager) in Web Of Science. Results/discussion: Iron supplementation is associated with a significant improvement in performance in athletes with a lack of this mineral. Creatine is well tolerated and can act as an ergogenic substance. Conclusion: There is little evidence about the benefits of supplementation in adolescent athletes and the decision must be individually considered and monitored by a health professional.